A list of highly influential biomedical researchers, 1996–2011. (21st October 2013) - Boyack, Kevin W.; Klavans, Richard; Sorensen, Aaron A.; Ioannidis, John P.A.
Abstract We have generated a list of highly influential biomedical researchers based on Scopus citation data from the period 1996‐2011. Of the 15, 153, 100 author identifiers in Scopus, approximately 1% (n=149, 655) have an h‐index >=20. Of those, we selected 532 authors who belonged to the 400 with highest total citation count (>=25, 142 citations) and/or the 400 with highest h‐index (>=76). Of those, we selected the top‐400 living core biomedical researchers based on a normalized score combining total citations and h‐index. Another 62 authors whose focus is outside biomedicine had a normalized score that was at least as high as the score of the 400th core biomedical researcher. We provide information on the profile of these most influential authors, including the most common Medical Subject Heading terms in their articles that are also specific to their work, most common journals where they publish, number of papers with over 100 citations that they have published as first/single, last, or middle authors, and impact score adjusted for authorship positions, given that crude citation indices and authorship positions are almost totally orthogonal. We also show for each researcher the distribution of their papers across 4 main levels (basic‐to‐applied) of research. We discuss technical issues, limitations and caveats, comparisons against other lists of highly‐cited researchers, and potential uses of this resource.